Nitrogênio e potássio na adubação do cártamo cultivado em latossolo vermelho - Anicésio, Ellen Cristina Alves de (2014)
Safflower (Carthamus tinctorius L.) is a promising crop to disseminate in Brazil for biodiesel production. However, the lack of basic knowledge about cultivation techniques, such as the nutritional requirement of the crop, are still obstacles to it’s expansion. Nitrogen and potassium are the nutrients that are extracted in greater amounts by plants, and their availability and the proper proportion between these nutrients in the soil are important factors in plant development. Thus, the objective was to study the effect of the combined rates of nitrogen and potassium on fertilization in safflower that is grown in Oxisol. This experiment was performed in a greenhouse using Oxisol that was collected under Cerrado vegetation in the 0-0.2-m layer. The experimental design was randomized blocks, and the treatments were arranged in a 5×5 factorial scheme, corresponding to five nitrogen rates (0, 60, 120, 180 and 240 mg dm-3) and five potassium rates (0, 50, 100, 150 and 200 mg dm-3) with four replications. At 55 days after plant emergence, the first experimental evaluation was performed, where the following were analyzed, phytometric characteristics: number of leaves, plant height and stem diameter; nutritional: chlorophyll index; and water consumption. At 74 days after emergence, in addition to the variables of the first evaluation, the following were determined, phytometric characteristics: number and diameter of heads; productive: dry mass of the aerial part, heads, roots and total; nutritional: concentration and accumulation of nitrogen and potassium in aerial part and heads; and efficient of water use. The results were analyzed by the response surface through the "Statistical Analysis System" (SAS, 2002). There was no significant interaction between nitrogen and potassium, with an isolated effect of factors for all of the variables at 55 and 74 days after emergence. Fertilization with nitrogen increased the number of leaves and the stem diameter in both of the evaluations. The chlorophyll index was positively influenced by nitrogen fertilization in both evaluations, with highest value found at a nitrogen rate of 168 mg dm-3. The number and diameter of the heads; the dry mass of the aerial part, heads, and total; and the efficiency of water use adjusted the regression quadratic model to nitrogen fertilization, with higher resulting nitrogen rates at 137, 122, 95, 124, 102 and 82 mg dm-3, respectively. The nitrogen concentration in the aerial part and in the heads adjusted the regression linear model; however, the higher nitrogen accumulation in aerial part and heads were provided by nitrogen doses of 169 and 154 mg dm-3, respectively; the highest potassium accumulation in aerial part and heads were found at nitrogen rates of 90 and 108 mg dm-3, respectively. The potassium fertilization had an isolated effect for all of the variables except for the chlorophyll index and head diameter with linear increasing. The nitrogen and potassium fertilization, in isolation, positively influences the phytometric characteristics, productive and nutritional of safflower plants after 55 and 74 days of cultivation.